PENGARUH ATMOSFER GERAI DAN PELAYANAN RITEL TERHADAP NILAI HEDONIK DAN PEMBELIAN IMPULSIF PELANGGAN MATAHARI DEPARTMENT STOREDUTA PLAZA DI DENPASAR - Ni Nyoman Manik Yistiani; Ni Nyoman Kerti Yasa; I G. A. Ketut Gede Suasana (Faculty of Economics and Business Udayana University, 2012)
The purpose of this research to determine the effect of atmospheric outlet and retail services toward impulsive buying through hedonic value. In this research examined four variables, namely atmospheric outlet, retail services, hedonic value as well as impulsive buying. The location of this research is at Matahari Departement Store Duta Plaza, in Denpasar with the target of population who purchase more than two times. The sample is taken by purposive sampling method.Based on Slovin formula, the number of sample about 168 consumer.Statistical Analysis was used to the test the hypothesis is Equation Model Structure (SEM). The main finding showed that the better atmospheric outlet will increase hedonic value and impulsive buying. Similarly,the better retail service will increase hedonic value and impulsive buying, but hedonic value not able to act as pemediasi of the relationship between atmospheric outlet and retail services toward impulsive buying. Therefore from the side of Matahari Departement Store Duta Plaza, Denpasar is expected to pay more attention to its atmospheric outlet and retail service in order to increase hedonic value and impulsivebuying